IR absorption spectra of lithium and silver vanadium-tellurite based glasses - Frechero, Marisa Alejandra (2007)
The aim of the present paper is to give structural information in order to set a correlation between the electrical conductivity behavior and structures of lithium and silver vanadium-tellurite based glasses. We report our structural studies and compare the effect of the nature of the metallic cation on glasses of the form XM2O · (1 - X)V2O5 · 2TeO2 (where 0 ≤ X < 1 and M = Li or Ag). Fourier transform infra-red (FTIR) spectra were recorded for all compositions and complementary differential scanning calorimetry (DSC) measurements and X-ray diffraction (XRD) measurements were also carried out. This paper should be considered as complementary to a previous article reporting the conductive behavior of theses glasses. In the latter we reported the obtained results on electrical conductivity studies. The results confirm the existence of a transition from a typically electronic (polaronic) conductive regimen when the molar fraction (X) of M2O is equal to 0, to an ionic conductive regimen when X tends to 1. The evidence for the independent migration path for both electrons and ions was put into evidence by studying the electrical conductivity behavior in a complementary system of the form X M2O · (1 - X)[0.5V2O5-0.5MoO3] · 2TeO2. In this system vanadium was partially replaced by molybdenum which acts as a 'diluting' agent of the active centers involved in the electronic transport.